Simultaneously Excited Downshifting/Upconversion Luminescence from Lanthanide‐Doped Core/Shell Fluoride Nanoparticles for Multimode Anticounterfeiting. (1st March 2018) - Liu, Jing; Rijckaert, Hannes; Zeng, Min; Haustraete, Katrien; Laforce, Brecht; Vincze, Laszlo; Van Driessche, Isabel; Kaczmarek, Anna M.; Van Deun, Rik
Abstract: This work presents a novel anticounterfeiting strategy based on a material changing its emission color in response to a change in the excitation sources—where a single ultraviolet (UV) or near‐infrared (NIR) light source are employed or simultaneously using two excitation sources (xenon lamp and NIR laser). Following this approach, various combinations of lanthanide (Ln 3+ )‐doped LiLuF4 /LiYF4 core/shell nanoparticles are prepared, providing a promising route to design flexible nanomaterials, as well as already a small library of luminescent materials, which change color when varying the excitation source (UV, NIR or both UV and NIR). Aside from excitation source‐dependent color change, these materials additionally show excitation‐source power‐dependent color change. This work exploits the possibility of developing a new class of multimode anticounterfeit nanomaterials, with excellent performance, which would be almost impossible to mimic or replicate, providing a very high level of security. Abstract : Lanthanide‐doped rare‐earth fluoride core/shell nanoparticles are prepared showing color‐tunable luminescence through a combination of upconversion and downshifting. LiLuF4 cores doped with either Er/Yb, Ho/Yb, or Tm/Yb, covered with an LiYF4 shell doped with either Eu/Ce or Tb/Ce show upconversion and/or downshifting luminescence upon simultaneous UV/NIR excitation by a xenon lamp and a power‐tunable 975 nm continuous‐wave laser.